Extraction of biologically active substances from peach kernels and use as an additive in the food industry - Eshmatov Fozil Xidirovich; Rejepov Quralbay Jadigerovich; Ismoilov Jasur Azizbek o’g’li (Zien Journals, 2022)
In the next stage of our research, we studied the fatty acid content of proteins, vitamins, minerals and fats from biologically active substances isolated from peach seeds grown in the climatic conditions of Uzbekistan. To do this, we synthesized methyl esters of fatty acids from the studied oils under alkaline conditions.
Keywords: Peach seeds; pressing; extraction; Soxlet